Genome-wide identification and comparative analyses of key genes involved in C4 photosynthesis in five main gramineous crops - Chen, Liang; Yang, Yang; Zhao, Zhangchen; Lu, Shan; Lu, Qiumei; Cui, Chunge; Parry, Martin A. J.; Hu, Yin-Gang (Frontiers in Plant Science, 2023)
Compared to C3 species, C4 plants have higher photosynthetic capacity and water and nitrogen use efficiency due to the presence of C4 photosynthetic pathway. Previous studies have shown that all genes required for the C4 photosynthetic pathway exist in the genomes of C3 species and expressed. In this study, the genes encoding six C4 photosynthetic pathway key enzymes (CA-β, PEPC, ME, MDH, RbcS) in the genomes of five important gramineous crops (C4: maize, foxtail millet, sorghum; C3: rice, wheat) were systematically identified and compared. Based on sequence characteristics and evolutionary relationships, their C4 functional copies were distinguished from non-photosynthetic functional copies. Furthermore, multiple sequence alignment revealed important sites for the major carboxylases/subunits for PEPC and RbcS activities between the C3 and C4 species. Comparison on expression characteristics confirmed that the expression patterns of non-photosynthetic copies were relatively conserved among species, while C4 copies in C4 species acquired new tissue expression patterns during evolution. Additionally, multiple sequence features that may affect C4 gene expression and subcellular localization were found in the coding and promoter regions. Our work emphasized the diversity of the evolution of different genes in C4 photosynthetic pathway, and confirmed that the specific high expression in leaf and appropriate intracellular distribution were the keys to the evolution of C4 photosynthetic. This study will help to analyze the evolutionary mechanism of the C4 photosynthetic pathway in gramineae, and provide reference for the transformation of C4 photosynthetic pathways in wheat, rice and other major C3 cereal crops.